2017
DOI: 10.1016/j.ajur.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

An update on transurethral surgery for benign prostatic obstruction

Abstract: Clinical benign prostatic hyperplasia (BPH) is one of the most common cause of lower urinary tract symptoms and transurethral resection of prostate (TURP) has been the gold standard technique for surgical treatment of benign prostate obstruction (BPO) over the last 2 decades. Although monopolar TURP is considered a safe and effective option for surgical management of BPO, there are some disadvantages, namely bleeding, transurethral resection syndrome, incompleteness of treatment. This review aims to highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…68 Unfortunately, studies describing the impact of TURP on social function is insufficient. 13 "Role functioning" was described as a core construct of HRQoL encompassing aspects of occupational and social roles that important for patients in all given treatment phases and for those as survivors from a particular disease.…”
Section: Functional Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…68 Unfortunately, studies describing the impact of TURP on social function is insufficient. 13 "Role functioning" was described as a core construct of HRQoL encompassing aspects of occupational and social roles that important for patients in all given treatment phases and for those as survivors from a particular disease.…”
Section: Functional Statusmentioning
confidence: 99%
“…73 To be exact, developing more effective nursing interventions focusing on functional status are possible to prevent TURP syndrome and deterioration of HRQoL. 13…”
Section: Functional Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, post-procedure complications occurred quite frequently, with early complications of bleeding, sepsis, electrolytes imbalance, TUR syndrome, incontinence, and urinary retention (3). In the past few decades, there has been considerable decrement in the incidence of these early complications mainly due to standardization of the procedure, and improvement in equipment, perioperative management, and anesthetic techniques (4). Although bleeding is the most important complication of TURP (5), a combined data from 10654 procedures reported that only 2.9% cases required transfusion due to bleeding (6).…”
Section: Introductionmentioning
confidence: 99%